Genetic ancestry shapes dengue virus infection in human skin explants - Priscila M. S. Castanha; Michelle M. Martí; Parichat Duangkhae; Jocelyn M. Taddonio; Kristine L. Cooper; Megan Wallace; Gwenddolen Kettenburg; Geza Erdos; Hasitha Chavva; Aleena Alex; J. Peter Rubin; Simon C. Watkins; et al. (Proceedings of the National Academy of Sciences, 2025)
Dengue is the most prevalent arthropod-borne viral disease of humans, with over half the world’s population at risk. Infection with any of the four dengue virus (DENV) serotypes is most often self-limiting, but a significant number of cases present with severe dengue characterized by vascular leakage that may be fatal. African ancestry is associated with protection against severe dengue, but the mechanisms are unknown. Using skin explants from genetically defined donors, we show that European ancestry skin has a much stronger inflammatory response to DENV than African ancestry skin, eliciting markedly increased infiltration, infection and migration of resident Langerhans cells, macrophages, and dendritic cells. The effect was seen with all dengue serotypes and Zika virus and in the presence of heterotypic immune serum. Genetic pathways associated with inflammation, interferon (IFN)-α, and inflammatory cytokine signaling were enriched in European relative to African ancestry skin following infection. Infiltration and infection of macrophages in African ancestry skin increased to that of European skin after blocking IFN-α and providing interleukin-1β. Polymorphic variants in RXRA , OAS1-3, and TGFB1 genes that were more frequent in European donors were associated with increased virus replication. Paradoxically, European ancestry skin cells had increased expression of OAS3 in response to virus and type I IFN. Thus, the limited inflammatory response of African ancestry skin to infection restricts replication and spread of dengue and other flaviviruses. Genetic ancestry should be considered when predicting a patient’s likelihood of severe dengue, and when assessing efficacy and adverse events associated with dengue vaccines.